Implementation of Humanistic Theory in ISMUBA Curriculum Development at Muhammadiyah Schools in Yogyakarta - Mohammad Qosim; Azam Syukur Rahmatullah (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2025)
This study is motivated by the importance of developing the Al-Islam and Kemuhammadiyahan (AIK) curriculum in Muhammadiyah schools, which should not only focus on cognitive aspects but also on shaping social attitudes, mutual respect, and Islamic brotherhood. This research aims to explore the implementation of humanistic theory, particularly the ideas of Carl R. Rogers, in developing the AIK curriculum in Muhammadiyah schools in Yogyakarta. This research employed a descriptive qualitative approach with an ethnomethodological method. Data were collected through interviews with AIK teachers who applied humanistic theory in the classroom and observations of teaching practices within the school environment. The findings reveal that AIK teachers in Yogyakarta have generally implemented a humanistic approach by providing role models, fostering social concern, and guiding students personally to prevent them from engaging in negative behaviors. The focus of learning is not limited to knowledge transfer but also emphasizes the development of students’ social and moral potential. In conclusion, applying humanistic theory in the AIK curriculum has proven effective in creating a humanistic learning climate, strengthening Islamic character, and enhancing students’ social awareness in Muhammadiyah schools. The implication of this study highlights the need for continuous teacher training in applying a humanistic approach. Further research is recommended to conduct comparative studies across different educational levels or to expand the number of respondents to enrich the findings.